(3aGYdjI HQfGeL eMGcGI dJfejI egGQGJ GfTGA THcGJ GdMGSH dOi WdGH TYHI GYOGO eYde GdMGShH (B/ s - (3QTG eMeO GdLeGd s; (3Ged YHOGdaJGM ShjOGf (B: s; (3eUWai YHOGdSejY eMeO (B: s ((3GdbGgQI (B: s (3QTG eMeO GdLeGd (B: s, 2009)
(3JgOa GdQSGdI ddJYQa Ydi eOi aGYdjI HQfGeL eMGcGI dJfejI egGQGJ GfTGA THcGJ GdMGSH hPdc HGdJWHjb Ydi (B60 (3WGdH ai TYHI eYde GdMGSH ebSejf deLehYI VGHWI heLehYI JLQjHjI dPdc HGSJNOGe GSJHGfI dGSJWdGY GQGA GdeJNUUjf fMh GdegGQGJ GdefGSHI dGfTGA GdTHcGJ hbGFeI HGdegGQGJ GddGReI dGfTGA GdTHcGJ hGNJjGQ JMUjd eYQai degGQGJ GfTGA GdTHcGJ hHWGbI edGMXI GdegGQGJ GdYdejI hbO GSaQJ GdfJGFL Yf aGYdjI HQfGeL GdeMGcGI dJfejI egGQGJ GfTGA THcGJ GdMGjHs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ GdJQHhjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeMGcGIs; (3GdegGQIs; (3THcGJ GdMGSHs